METHODS OF STAPLING WOOL FIBERS AND SPINNING THEM - Turdiyev Raxmatulla Muhammadali o‘g‘li (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: This article provides information on the steps involved in stapling wool fibers and spinning them into yarn. As part of the work carried out at the enterprise, information on cutting wool fiber into 6-7 cm length and spinning high-quality yarn from it was presented.